Long-lived charged states of single porphyrin-tape junctions under ambient conditions - Leary, E; Kastlunger, G; Limburg, B; Rincón-García, L; Hurtado-Gallego, J; González, MT; Bollinger, GR; Agrait, N; Higgins, SJ; Anderson, HL; Stadler, R; Nichols, RJ (Royal Society of Chemistry, 2020)
The ability to control the charge state of individual molecules wired in two-terminal single-molecule junctions is a key challenge in molecular electronics, particularly in relation to the development of molecular memory and other computational componentry. Here we demonstrate that single porphyrin molecular junctions can be reversibly charged and discharged at elevated biases under ambient conditions due to the presence of a localised molecular eigenstate close to the Fermi edge of the electrodes. In particular, we can observe long-lived charge-states with lifetimes upwards of 1–10 seconds after returning to low bias and large changes in conductance, in excess of 100-fold at low bias. Our theoretical analysis finds charge-state lifetimes within the same time range as the experiments. The ambient operation demonstrates that special conditions such as low temperatures or ultra-high vacuum are not essential to observe hysteresis and stable charged molecular junctions.